PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MEDIASI KEPUASAN KERJA PADA UD. ROMO JEWELRY MANUFACTURER DI GIANYAR - I Komang Dwi Yasa; Made Astrama (Forum Manajemen, 2018)
The purpose of this study is to determine the direct effect of compensation on employee performance, the effect of compensation on job satisfaction, the effect of job satisfaction on employee performance and to determine the effect of compensation on employee performance through mediation employee job satisfaction. The analysis technique used is path analysis which is accompanied by Sobell test (Sobell test). Based on the result of path analysis found that the indirect influence of compensation on employee performance through mediation of job satisfaction is higher that is 0,545 compared to direct influence of compensation to employee performance that is 0,091. While through test sobell (Sobell test) found that the compensation has a significant positive effect on employee performance seen from the significance value of the research of (0.001 <0.05), compensation has a significant positive effect on job satisfaction seen from the significance value of research (0.000 <0.05), job satisfaction has a significant positive effect on employee performance as seen from significance value of research (0,000 <0,05) and compensation has positive significant effect on employee performance through job satisfaction mediation seen from value of Zhitung (6,882)> Ztabel (1,96).